2007
DOI: 10.1016/j.jom.2007.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the field of operations management

Abstract: This Special Issue of the Journal of Operations Management consists of 16 articles by 26 authors covering Operations Managements (OM) topics and issues from the 16th century to the 21st with predictions for the future. While it does not pretend to be comprehensive, it is representative of the types of subjects of inquiry through out this historical period in what could be considered OM. This introduction attempts to put the papers in context, and concludes with comments about what might be considered fundament… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0
13

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(55 citation statements)
references
References 30 publications
0
42
0
13
Order By: Relevance
“…Operations management scholars started focusing on quality in the 19th and early 20th century (Sprague, 2007) including the quality circle and quality management movements, JIT/Lean, the cost of quality and design for manufacture and assembly (Sprague, 2007), measuring and control of service quality, strategic issues of quality in services (Machuca et al, 2007), six sigma, net promoter system process improvement Wu and Wu (2015). Recently, Yee et al (2010) found that employee loyalty is considerably related to service quality, which in turn will have an impact on both customer satisfaction and customer loyalty, which ultimately will lead to firm profitability in high-contact service industries (Yee et al, 2010).…”
Section: Service Quality In Operationsmentioning
confidence: 99%
“…Operations management scholars started focusing on quality in the 19th and early 20th century (Sprague, 2007) including the quality circle and quality management movements, JIT/Lean, the cost of quality and design for manufacture and assembly (Sprague, 2007), measuring and control of service quality, strategic issues of quality in services (Machuca et al, 2007), six sigma, net promoter system process improvement Wu and Wu (2015). Recently, Yee et al (2010) found that employee loyalty is considerably related to service quality, which in turn will have an impact on both customer satisfaction and customer loyalty, which ultimately will lead to firm profitability in high-contact service industries (Yee et al, 2010).…”
Section: Service Quality In Operationsmentioning
confidence: 99%
“…Managing processes and operations in organizations has been an enduring theme in management/organizational research (Craighead and Meredith 2008;Gupta et al 2006;Sprague 2007;Voss 2007). Much of the work is founded on the technical principles of Frederick Taylor's "Scientific Management'' whose roots go back over a hundred years (Wilson 2003).…”
Section: Production Tqm Project Managementmentioning
confidence: 99%
“…Neste mesmo primeiro volume do JOM, Chase (1980) publicou um trabalho sobre a evolução e classificação da pesquisa em Gestão de Operações com base em artigos contidos em quatro periódicos de renome: Decision Sciences, AIIE Transactions, Management Science e International Journal of Production Research. Mais recentemente, em 2007, o periódico JOM destinou um número especial, com 16 artigos, à análise dos tópicos abordados pela Gestão de Operações, considerando sua evolução histórica desde o século XVI até o XXI (Sprague, 2007).…”
Section: A Pesquisa Científica Sobre Gestão De Operaçõesunclassified